Knowledge Management in the Palestinian Higher Education: A Research Agenda - Abdullah Waleed Almudallal; Syaharizatul Noorizwan Muktar; Norhani Bakri (International Review of Management and Marketing, 2016)
This research tries to highlight on how Knowledge Management (KM) will act as a good tool to connect all the University's Stakeholders such as: students, teachers, researchers, business and external entities, with work processes and technologies. Today, the quality of Higher Education in developing countries has become more complex as they have to keep pace and compete with the International HEIs Standards. The purpose of this research is to provide empirical evidence that increases an understanding of KM practices in HEIs within the context of instable environments, focusing on the unique geopolitical situation of the occupied Palestine. A primary focus of this paper is to investigate the social phenomenon without explicit expectations or early assumptions, asking a deep qualitative questions of ‘why' people of Palestine look for knowledge, ‘how' they use this knowledge, and ‘how' they face the instability of the complicated situation in order to develop a knowledge society.